Effectivity of Gel Ethanolic Extract of Senggani Leaves (Melastoma candidum D. Don) In Increasing The Number of Fibroblast Cells and Thickness of Collagen Fibers Against Socket Wound after Tooth Extraction on Male White Rats - Halim, Susanna; Girsang, Ermi; Ehrich Lister, I Nyoman; Nasution, Ali Napiah (American Scientific Research Journal for Engineering, Technology, and Sciences, 2019)
The important cells in wound healing process are the fibroblast cells and the density of collagen fibers. The Senggani leaves (Melastoma candidum D.Don) contains some active compound of flavonoids / phenols, triterpenoid / steroid, saponins, tannins and glycosides. This research aims to determine the effectiveness of gel ethanolic of Senggani leaves (Melastoma candidum D.Don) towards increased number of fibroblast cells and collagen density score in the process of wound healing after tooth extraction on male white rats (Rattus noevegicus). The research design was purely experimental in vivo, design post test only control group and non – randomly or non – probability sampling using the sample of 25 Wistar rats. Male white rats anesthetized intra-peritoneal (IP) using ketamine 100 mg / 1 ml at a dose of 20-40 mg/kg body weight of the rat, then extraction of the mandibular left incisor using a sharp excavator and pulling the pliers off, then Dental sockets are irrigated with a sterile was given Aloclair Plus gel ®, the treatment group was given 1% EDS, 5% EDS and 10% EDS twice a day with a frequency of 12 times the treatment.On the seventh day, euthanasia was carried out, the rats were put into a closed box containing ether cotton until suffocation, followed by histological tissue making. Histology preparations were seen with the Boeco Binocular microscope BM-180 SP model, with the help of MDCE-5A digital microscope camera connected to a binocular microscope through the eyepiece entry hole, and using a 10 x objective lens and analyzed using Adobe Photoshop CS 6.0 software to view a number of fibroblast cells and density of collagen fibers. Calculations were carried out with 5 fields of view then calculated how many fibroblasts and collagen density scores in each field of view so that they were clearly visible. From the field of view 1 to 5 it is added up, taken the average. The results of descriptive analysis of the number of fibroblast cells and collagen fiber density scores showed that the average number of fibroblast cells and the highest collagen fiber density score in the 10% EDS treatment group were 83,133 and 3,933, followed by the positive control group of 82,667 and 3,667, the 5% EDS treatment group is 41,200 and 3,067, the EDS treatment group is 1% which is 33,800 and 3,000, and the lowest result is negative control which is 16,533 and 1,200.  Data analysis was using Shapiro Wilk normality test, Levene homogeneity test, One way Anova test and the test of the comparative effect (LSD = Least Significant Difference and Tukey's HSD = Honestly Significant Difference). The results showed that has normal distribution of data (p > 0,05) and homogeneity of data (p> 0,05). One way annova test results the significant number of fibroblast cells and collagen fiber density score on the  fifth group (given Melastoma candidum D. Don rind extract gel concentration of 10 %). The conclusion showed that Melastoma candidum D. Don rind extract gel concentration of 10 % is effective towards increased the number of fibroblast cells and thickness of collagen fibers score against socket wounds after tooth extraction in male white rats.